PEMAHAMAN KOMPREHENSIF TENTANG PEMBELAJARAN MANUSIA - Fariza, Fariza Zulfalillah; Herdiana, Dodi (Journal of Education, 2024)
Humans as learners are required to actively participate in learning activities so that they can acquire knowledge, skills, and attitudes that can improve themselves. Since the 19th century, many theories about learning have been created, and each theory has a different perspective, foundation, epistemology, and content. This research focuses on providing an understanding of learning, learning theories according to experts, factors that influence learning, and challenges faced in learning. These things need to be studied more deeply by an educator to gain knowledge that can help in providing good learning and providing a memorable learning experience. The research method used is library research by collecting literature sources in the form of books and journals related to the topic of human learning. Key words: learning, human learning